Interval between IVF stimulation cycle and frozen embryo transfer: Is there a benefit to a delay between cycles?. (14th September 2017) - Higgins, Chloe; Healey, Martin; Jatkar, Sameer; Vollenhoven, Beverley
Abstract : Background: There is currently limited evidence available regarding ideal timing for frozen embryo transfer (FET). Demonstrating that delaying FETs has few clinical benefits would allow patients to proceed with FET at their earliest convenience. Aims: To examine whether the time interval between stimulation cycle and subsequent FET affects pregnancy and live birth rates. Materials and methods: This retrospective cohort study, based in a multi‐site private in vitro fertilisation (IVF) clinic categorised women into two groups: those having FET cycles administered within 25–35 days or 50–70 days of IVF stimulation cycle and embryo freeze. Outcomes measured were clinical pregnancy and live birth rates. Results: When comparing the patients who have had a 25–35 days gap between embryo freeze and FET, to the matched patients who had a 50–70 days gap, the statistically significant results showed an adjusted odds ratio for live birth of 1.31 (1.02–1.67). The adjusted odds ratio for clinical pregnancy in matched case : control analysis was not statistically significant at 1.22 (0.97–1.53). Conclusion: A gap of 25–35 days between embryo freeze and FET was associated with improved live birth rates compared to a gap of 50–70 days.